The Effectiveness of Mindfulness in Improving Self-Regulation in Gadget-Addictive Adolescents - Fifin Dwi Purwaningtyas; Aironi Zuroida; Lutfiana Nurlaily; Bayu Andriyani Wahyuning Lestari (Program Studi Psikologi, Fakultas Ilmu Sosial dan Ilmu Politik, Universitas Mulawarman, 2025)
The increasing excessive use of gadgets among adolescents has led to a tendency toward addictive behavior, impacting psychological well-being and weakening emotional regulation. This situation demands effective psychological interventions to help adolescents manage themselves more adaptively. This study aims to test the hypothesis that these interventions, Mindfulness Attention Awareness, are effective in increasing mindfulness levels in adolescents with gadget addiction. The study used a quantitative approach with an experimental design. One group pretest-posttest research subjects were 25 teenagers aged 14–19 years who were screened using the Smartphone Addiction Scale–Short Version (SAS-SV). The intervention was administered over three weeks in six sessions (twice per week) with a duration of 60–90 minutes per session. The intervention materials included mindful breathing exercises, body scan, observation of thoughts and emotions, and the development of self-compassion. The mindfulness measurement instrument uses the Mindfulness Attention Awareness Scale (MAAS). The normality and homogeneity tests show that the data are normally and homogeneously distributed. The test results, paired sample t-testshowed a significant difference between the pretest and posttest scores (t(24) = -46.850, p = 0.000). This finding supports the hypothesis that the intervention Mindfulness Attention Awareness is effective in increasing full awareness and helping teenagers reduce the tendency towards addictive behavior towards gadgets.Fenomena meningkatnya penggunaan gadget secara berlebihan pada remaja telah menimbulkan kecenderungan perilaku adiktif yang berdampak pada kesejahteraan psikologis dan melemahkan fungsi regulasi emosi. Kondisi ini menuntut adanya intervensi psikologis yang efektif untuk membantu remaja mengelola diri secara lebih adaptif. Penelitian ini bertujuan untuk menguji hipotesis bahwa intervensi Mindfulness Attention Awareness efektif dalam meningkatkan tingkat mindfulness pada remaja yang mengalami kecanduan gadget. Latar belakang penelitian ini didasarkan pada meningkatnya fenomena perilaku adiktif terhadap penggunaan gadget pada kalangan remaja yang berdampak pada kesejahteraan psikologis dan fungsi regulasi emosi. Penelitian ini menggunakan pendekatan kuantitatif dengan desain eksperimen one group pretest-posttest. Subjek penelitian berjumlah 25 remaja berusia 14–19 tahun yang disaring menggunakan Smartphone Addiction Scale–Short Version (SAS-SV). Intervensi diberikan selama tiga minggu dalam enam sesi, dua kali per minggu, dengan durasi 60–90 menit per sesi. Materi intervensi berbasis modul meliputi latihan pernapasan sadar, pemindaian tubuh (body scan), pengamatan pikiran dan emosi, serta pengembangan self-compassion. Instrumen pengukuran mindfulness menggunakan Mindfulness Attention Awareness Scale (MAAS). Uji normalitas dan homogenitas menunjukkan bahwa data berdistribusi normal dan homogen. Hasil uji paired sample t-test menunjukkan perbedaan yang signifikan antara skor pretest dan posttest (t(24) = -46.850, p = 0.000). Hasil ini mendukung hipotesis bahwa intervensi Mindfulness Attention Awareness efektif dalam meningkatkan kesadaran penuh dan membantu remaja dalam mengurangi kecenderungan perilaku adiktif terhadap gadget.